Comparative analysis of wild and cultivated Lathyrus L. species to assess their content of sugars, polyols, free fatty acids, and phytosterols - A. E. Solovyeva; T. V. Shelenga; A. L. Shavarda; M. O. Burlyaeva (Вавиловский журнал генетики и селекции)
Under climate change, the need for crops resistant to abiotic and biotic stresses increases. Lathyrus spp. Are characterized by a high nutritional value of their green biomass. The grass pea is one of the most resistant to drought, aterlogging, cold, salinity, diseases and pests among cultivated legumes, and it is grown at minimal cost. The development of new Lathyrus cultivars with an improved composition of nutrients will make it possible to produce high-quality animal feed in areas with extremely unstable weather conditions. With this in view, the patterns of variability in the parameters of the carbohydrate complex (sugars, their lactone and methyl forms), polyols (including phenol-containing alcohols), phytosterols, free fatty acids (FFA) and acylglycerols were studied in the green biomass of 32 accessions representing Lathyrus sativus L., L. tuberosus L., L. sylvestris L., L. vernus (L.) Bernh., L. latifolius L. and L. linifolius (Reichard) Bassler. from the VIR collection, reproduced in Leningrad oblast under contrasting conditions of 2012 and 2013. The content of identified compounds varied depending on the genotype, species, and weather. High temperatures and high precipitation in 2013 contributed to the accumulation of monosaccharides, and the colder and drier conditions of 2012 to an increase in oligosaccharides, most polyols, and FFA. The cultivated species (L. sativus) was distinguished by its high sugar content, and the wild species as follows: L. latifolius by FFA; L. linifolius by ononitol, myo-inositol, and glycerol 3-phosphate; L. vernus by MAG and methylpentofuranoside. The resulting data showed that the Lathyrus accessions studied are promising for breeding stress-resistant cultivars of high nutritional quality.